2011
DOI: 10.4321/s0004-05922011000400008
|View full text |Cite
|
Sign up to set email alerts
|

Glutamina e nucleotídeos na dieta de frangos de corte criados no sistema alternativo

Abstract: RESUMOObjetivou-se avaliar o efeito da suplementação com glutamina e nucleotídeos na dieta sobre o desempenho e morfologia da mucosa intestinal de frangos de corte criados no sistema alternativo. Foram utilizados 600 pintos de corte machos distribuídos em delineamento em blocos casualizados, no esquema fatorial 3x2 (três níveis de glutamina: 0,0; 0,5 e 1,0% e dois níveis de nucleotídeos purificados na dieta: 0,0 e 0,04%), totalizando 6 tratamentos, com 4 repetições de 25 aves cada. Foram obtidos os dados de de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 8 publications
1
5
0
8
Order By: Relevance
“…Las aves sujetas a muda forzada experimentan una regresión y atrofia severa de los tejidos, en particular una alteración en la integridad de la superficie de absorción intestinal que disminuye la capacidad de absorción y digestión (Ferrer et al, 1995;Macari, 1998;Pelicano et al, 2003;Maiorka, 2004;Zavarize et al, 2011). Los aminoácidos condicionalmente esenciales como la glutamina pueden ser sintetizados en cantidades adecuadas por los animales, pero necesitan ser suministrados en la dieta cuando las tasas de utilización tienen un incremento relativo a las tasas de síntesis (Neu et al, 1996;Kim et al, 2007).…”
Section: Introductionunclassified
“…Las aves sujetas a muda forzada experimentan una regresión y atrofia severa de los tejidos, en particular una alteración en la integridad de la superficie de absorción intestinal que disminuye la capacidad de absorción y digestión (Ferrer et al, 1995;Macari, 1998;Pelicano et al, 2003;Maiorka, 2004;Zavarize et al, 2011). Los aminoácidos condicionalmente esenciales como la glutamina pueden ser sintetizados en cantidades adecuadas por los animales, pero necesitan ser suministrados en la dieta cuando las tasas de utilización tienen un incremento relativo a las tasas de síntesis (Neu et al, 1996;Kim et al, 2007).…”
Section: Introductionunclassified
“…Similarly, Maiorka et al (2000) did not find differences on performance of broilers fed 10.0g/kg L-glutamine during 1 to 7 days of age. Zavarize et al (2011) verified that glutamine supplementation (1%) improved body weight, feed intake and feed conversion in the first week of broiler chicks housed in alternative breeding system. The feed conversion ratio has improved linearly with L-glutamine supplementation (P<0.05) (Table 2, Figure 1).…”
Section: Resultsmentioning
confidence: 68%
“…This result was unexpected because glutamine is supposed to have an effect on cell proliferation. However, Zavarize et al (2011) reported that glutamine did not affect villi height and crypt depth of small intestine of 42-day-old broilers. Crypt depths in the duodenum, jejunum and ileum (Table 7) were significantly longer in 18 and 42-day-old birds fed diets supplemented with glutamine (P<0.05) (Figure 3,4,5,6,7 and 8 Considering broilers at 18 days of age, the better glutamine inclusion to improve crypt depth of duodenum and ileum was 20.0g/kg and to improve crypt depth of jejunum was 10.0g/kg.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Os dados encontrados concordam com Rutz et al (2006), em que observaram melhora no desempenho de frangos de corte ao fornecerem extrato de leveduras aos animais e atribuíram o melhor desempenho, ao efeito benéfico dos nucleotídeos presentes no extrato de leveduras. Por outro lado, Zavarize et al (2007) não observaram melhora no desempenho de frangos de corte recebendo dieta suplementada com 0,05% nucleotídeos quando comparado aos animais que receberam dieta não suplementada.…”
Section: Discussionunclassified